Inhibition of Alzheimer amyloid β aggregation by polyvalent trehalose - Yoshiko Miura et al (Science and Technology of Advanced Materials, 2008)
A glycopolymer carrying trehalose was found to suppress the formation of amyloid fibrils from the amyloid β peptide (1–42) (Aβ), as evaluated by thioflavin T assay and atomic force microscopy. Glycopolymers carrying sugar alcohols also changed the aggregation properties of Aβ, and the inhibitory effect depended on the type of sugar and alkyl side chain. Neutralization activity was confirmed by in vitro assay using HeLa cells. The glycopolymer carrying trehalose strongly inhibited amyloid formation and neutralized cytotoxicity.